The Analysis Of Humanity Values In Shakespeare’s Novel King Lear And Pedagogical Contribution - Budiyanto, Darmawan (JURNAL DIDASCEIN BAHASA, 2016)
ABSTRACT: The problems of this study are: 1) what are the humanity values found in Shakespeare’s novel King Lear? 2) what are the pedagogical contributions of the study to the learners as a literature?  The aims of the study are to describe the humanity values found in Shakespeare’s King Learand to describe pedagogical contributions of the study to the learners as a foreign language. This research are classified as qualitative research or used description and interpretation of the indications in main characters in the novel accurately. The library sources consist of primary and secondary data. The primary data were the novel and the secondary data were from books, magazines, non-printed sources on internet then data are gathered in description method. The result of the study shows that: 1) the elements of humanity values in Shakespeare’s Novel ‘King Lear include seven elements. They are as follows :(1) understanding, (2) bravery, (3) togetherness, (4) cooperation, (5) honesty, (6) patience, and (7) loyalty. 2) The result is the students thus may learn the use of the words they get themselves more effectively pedagogically. The value of literature does not goal only insight of humanity, but that of values for learning the English language in the classroom. Although pedagogy is sometimes seen as a nebulous concept, it is essentially a combination of knowledge and skills required for effective teaching. The more traditional definitions describe pedagogy as either the science/theory or art/practice of teaching that makes a difference in the intellectual and social development of students. Keywords:values in novel, pedagogical contributions